Health Conditions Of Indian Tribal Women – A Sociological Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
Good health status is a needed thing to all gender. The power, position, social status, social recognition, respect in family as well as society all determine the efficient health status of an individual. Health condition encompasses the full freedom which an individual decides about their own body. If a woman is having the holistic liberty to control her own biological processes, it is being considered as successful autonomy of health. But in reality the hands of cultural and religious webs are indirectly controlling the women activities like domestic, social, political as well as their body too. Since the ancient period the woman did not have any rights over their health. The family system or the male members of the family were acted as the deciding authority over the health condition of women. The child marriages, early hood pregnancy, maternal death, passion of having male child, lack of malnutrition and attitude of patriarchal were the common things which were affected the health of the women in the past periods.The present study aims at exploring the health condition of Tribal women in India.